Broadband tunable electromagnetically induced transparency analogue metamaterials based on graphene in terahertz band. (17th May 2018) - Wang, Yue; Leng, Yanbing; Wang, Li; Dong, Lianhe; Liu, Shunrui; Wang, Jun; Sun, Yanjun
Abstract: Most of the actively controlled electromagnetically induced transparency analogue (EIT-like) metamaterials were implemented with narrowband modulations. In this paper, a broadband tunable EIT-like metamaterial based on graphene in the terahertz band is presented. It consists of a cut wire as the bright resonator and two couples of H-shaped resonators in mirror symmetry as the dark resonators. A broadband tunable property of transmission amplitude is realized by changing the Fermi level of graphene. Furthermore, the geometries of the metamaterial structure are optimized to achieve the ideal curve through the simulation. Such EIT-like metamaterials proposed here are promising candidates for designing active wide-band slow-light devices, wide-band terahertz active filters, and wide-band terahertz modulators.